2022
DOI: 10.3390/w14050782
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Based Evaluation of Improvements in Drinking Water Treatment Using Cost-Benefit Analysis

Abstract: Reliable and safe drinking water supply requires adequate risk management. Decision support models can aid decisionmakers to effectively evaluate risk mitigation measures and allocate societal resources. Here, a Swedish case study illustrates how the installation of ultrafiltration membranes can be evaluated by combining risk assessment and cost-benefit analysis. Quantitative microbial risk assessment was used to assess several contamination sources and estimate the achieved risk reduction from waterborne path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…A cost benefit analysis on water treatment showed the benefits of the filters outweighed the costs only when including aesthetic benefits, not health benefits alone. 112 A cost-benefit analysis for a combined cookstove and water treatment intervention (an improved stove and water filter) in Rwanda showed that benefits from fuelwood savings, time savings, and environmental and health improvements outweighed the cost. 33 However, fuel savings among new water filter users were found only for households who previously boiled their water, not for households which had not treated their water previously.…”
Section: Discussionmentioning
confidence: 99%
“…A cost benefit analysis on water treatment showed the benefits of the filters outweighed the costs only when including aesthetic benefits, not health benefits alone. 112 A cost-benefit analysis for a combined cookstove and water treatment intervention (an improved stove and water filter) in Rwanda showed that benefits from fuelwood savings, time savings, and environmental and health improvements outweighed the cost. 33 However, fuel savings among new water filter users were found only for households who previously boiled their water, not for households which had not treated their water previously.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is presented in [170], combining QMRA and CBA to measure microbial health risks and socio-economic profitability. Moreover, in the process of drinking water treatment, the need for a holistic approach is emphasized.…”
Section: Drinking Water and Health Risksmentioning
confidence: 99%
“…Figure 3 shows 100 simulated TTS point processes starting from t 1 = 0. For the simulations, P s is randomly sampled from a uniform distribution of U ∼ [0, 1].…”
Section: Simulating a Tts Point Processmentioning
confidence: 99%
“…Water mains are key municipal infrastructure assets supporting the daily life of citizens [1]. Though water mains are designed to serve for several decades, they deteriorate with increasing service age, and can break before reaching the target design life.…”
Section: Introductionmentioning
confidence: 99%